Učinki vadbe na koordinacijo in spretnost roke v navideznem okolju pri bolnikih s Parkinsonovo boleznijo - Krizmanič, Tatjana (Rehabilitacija (Ljubljana), 2017)
Introduction: Virtual reality is a new treatment method which has been introduced also in rehabilitation. The main focus of the research was to examine the impact of virtual box computer game %10 cubes% in patients with PD on skills and co-ordination of their hands. Methods: Patients with Parkinson%s disease were referred to a regular rehabilitation program and were invited to participate in our research. They all have some difficulties with upper limbs while performing daily activities. For the research purpose, we designed the virtual box exercise. The aim of the exercise was to transfer 10 randomly placed virtual cubes into the box. The patients were evaluated before and after training sessions with Jebsen Hand Function Test, Nine Hole Peg Test, Box and Blocks Test, Unified Parkinson Disease Rating Scale % motor examination (UPDRS III). Results: Twenty-eight patients with PD were included, 12 males and 16 females, with mean age was 67 years (range from 49 to 80 years). Patients finished in ten sessions within the period of three weeks Each therapy lasted for 30 minutes. The therapy was divided into five repetitions, each was 2 minutes long. The outcomes in clinical tests demonstrated a slight improvement in hand function. Conclusion: The results show that performing hand skills and coordination with exergaming could be an additional program to the conventional rehabilitation for patients with PD. Functional tests revealed improvement in hand function. The patients showed great motivation.
Keywords: exercise; navidezno okolje; Parkinson Disease; Parkinsonova bolezen; Telerehabilitation; telesna vadba; upper limb; virtual environment; zgornji ud